2008
DOI: 10.1093/aob/mcn166
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus Enhances Al Resistance in Al-resistant Lespedeza bicolor but not in Al-sensitive L. cuneata Under Relatively High Al Stress

Abstract: P enhanced Al resistance in the Al-resistant L. bicolor species but not in the Al-sensitive L. cuneata under relatively high Al stress, although P in L. cuneata might also possess an alleviative potential. Enhancement of Al resistance by P in the resistant species might be associated with its more efficient P accumulation and translocation to shoots and greater Al exclusion from root tips after P application, but not with an increased exudation of organic acids from roots.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
38
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 62 publications
(44 citation statements)
references
References 33 publications
4
38
0
2
Order By: Relevance
“…of pummelo seedlings, as previously found for rice (Oryza sativa) (Nakagawa et al, 2003) and Lespedeza bicolor (Sun et al, 2008). Al decreased leaf and root P concentration ( Figure 2C and D), as previously reported for 'Nemaguard' peach (Prunus persica) (Graham, 2001), white lupin (Shane et al, 2003) and beech (Fagus sylvatica) (P ( ahlsson, 1990).…”
Section: Discussionsupporting
confidence: 86%
“…of pummelo seedlings, as previously found for rice (Oryza sativa) (Nakagawa et al, 2003) and Lespedeza bicolor (Sun et al, 2008). Al decreased leaf and root P concentration ( Figure 2C and D), as previously reported for 'Nemaguard' peach (Prunus persica) (Graham, 2001), white lupin (Shane et al, 2003) and beech (Fagus sylvatica) (P ( ahlsson, 1990).…”
Section: Discussionsupporting
confidence: 86%
“…Sun et al (2008) reported that phosphorus application alleviated Al toxicity in L. bicolor and decreased the exudation of organic acid anions under Al stress. The same phenomenon has also been found in other plant species (Gaume et al 2001;Dong et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence has shown that Al toxicity can be alleviated by P supply in some plants, including C. grandis [30, 31], sorghum [124], maize [102], and L. bicolor [125]. There are several authors investigating the effects of P on the Al-induced secretion of OA anions from roots, but the results are somewhat different.…”
Section: Aluminium-induced Secretion Of Organic Acid Anions From Rmentioning
confidence: 99%